PENGARUH SOCIAL MEDIA (INSTAGRAM) TERHADAP PURCHASE INTENTION DENGAN BRAND EQUITY SEBAGAI VARIABEL MEDIASI - Randy Admi; Jason Artha Usbay (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of social media (Instagram) on purchase intention with brand equity as a mediating variable. This type of research is a descriptive study with the study population, namely Indonesian citizens who use Instagram and obtained as many as 150 respondents through a sampling technique, namely purposive sampling with criteria 1. Indonesian citizens aged at least 18 years 2. Have purchased Compass Shoes and followers of the Compass Shoes Instagram account . The data analysis technique used in this study is PLS (partial least squares) and the results of the data analysis obtained that E-WOM has a positive and significant effect on purchase intention, User-generated social media communication has a positive and significant effect on E-WOM, Firm - the creation of social media communication has a positive and significant effect on E-WOM, and Brand Equity plays a significant role in mediating the relationship between E-WOM and Purschase Intention.